Anglikanie w Iranie w czasie Rewolucji Islamskiej = Anglicans in Iran during the Islamic Revolution - Rzepka, Marcin (Studia religiologica, 2016)
The Islamic Revolution had a great impact on defining the position of religious minorities in Iran. Christians belonging to ethnic churches - Armenians and Assyrians - obtained constitutional rights. Others, especially Anglicans, conducting missionary activity, faced restrictions and persecution such as confiscation of property and arrests caused by the revolutionary authorities. The article presents Anglicans’ attitudes toward the Islamic Revolution, taking into account the international context of events related to the imprisonment of British citizens in 1980 - employees of the Anglican Diocese of Iran. It tries to prove, in fact, profound changes, both quantitative and qualitative, within Christianity in the Islamic Republic of Iran.